Harmonization of Derivative Legislative Products Post-Constitutional Court Decision - Lubis, Arief Fahmi (PT. Riset Press International, 2025)
A ruling by the Constitutional Court constitutes a judicial product, necessitating harmonization and synchronization between the Constitutional Court's decisions and subordinate regulations. This process is essential for the legislative body to ensure legal coherence. This study aims to demonstrate that insufficient communication between institutions may impede the timely alignment and harmonization of laws amended by the Constitutional Court with regulations beneath the statutory level, thereby creating conflicts among legal provisions. This qualitative research employs a descriptive approach to systematically and factually collect data, reflecting the situation during the study. The findings underscore the critical need to harmonize derivative legal products after Constitutional Court rulings.